Role for Plant-Derived Antioxidants in Attenuating Cancer Cachexia - Wenlan Li; Kristy Swiderski; Kate T. Murphy; Gordon S. Lynch (MDPI AG, 2022)
Cancer cachexia is the progressive muscle wasting and weakness experienced by many cancer patients. It can compromise the response to gold standard cancer therapies, impair functional capacity and reduce overall quality of life. Cancer cachexia accounts for nearly one-third of all cancer-related deaths and has no effective treatment. The pathogenesis of cancer cachexia and its progression is multifactorial and includes increased oxidative stress derived from both the tumor and the host immune response. Antioxidants have therapeutic potential to attenuate cancer-related muscle loss, with polyphenols, a group of plant-derived antioxidants, being the most widely investigated. This review describes the potential of these plant-derived antioxidants for treating cancer cachexia.